Are WHO/UNAIDS/UNICEF-recommended replacement milks for infants of HIV-infected mothers appropriate in the South African context? - Papathakis P.C; Rollins N.C (The World Health Organization, 2004)
OBJECTIVE: Little is known about the nutritional adequacy and feasibility of breastmilk replacement options recommended by WHO/UNAIDS/UNICEF. The study aim was to explore suitability of the 2001 feeding recommendations for infants of HIV-infected mothers for a rural region in KwaZulu Natal, South Africa specifically with respect to adequacy of micronutrients and essential fatty acids, cost, and preparation times of replacement milks. METHODS: Nutritional adequacy, cost, and preparation time of home-prepared replacement milks containing powdered full cream milk (PM) and fresh full cream milk (FM) and different micronutrient supplements (2 g UNICEF micronutrient sachet, government supplement routinely available in district public health clinics, and best available liquid paediatric supplement found in local pharmacies) were compared. Costs of locally available ingredients for replacement milk were used to calculate monthly costs for infants aged one, three, and six months. Total monthly costs of ingredients of commercial and home-prepared replacement milks were compared with each other and the average monthly income of domestic or shop workers. Time needed to prepare one feed of replacement milk was simulated. FINDINGS: When mixed with water, sugar, and each micronutrient supplement, PM and FM provided <50% of estimated required amounts for vitamins E and C, folic acid, iodine, and selenium and <75% for zinc and pantothenic acid. PM and FM made with UNICEF micronutrient sachets provided 30% adequate intake for niacin. FM prepared with any micronutrient supplement provided no more than 32% vitamin D. All PMs provided more than adequate amounts of vitamin D. Compared with the commercial formula, PM and FM provided 8-60% of vitamins A, E, and C, folic acid, manganese, zinc, and iodine. Preparations of PM and FM provided 11% minimum recommended linoleic acid and 67% minimum recommended alpha-linolenic acid per 450 ml mixture. It took 21-25 minutes to optimally prepare 120 ml of replacement feed from PM or commercial infant formula and 30-35 minutes for the fresh milk preparation. PM or FM cost approximately 20% of monthly income averaged over the first six months of life; commercial formula cost approximately 32%. CONCLUSION: No home-prepared replacement milks in South Africa meet all estimated micronutrient and essential fatty acid requirements of infants aged <6 months. Commercial infant formula is the only replacement milk that meets all nutritional needs. Revisions of WHO/UNAIDS/UNICEF HIV and infant feeding course replacement milk options are needed. If replacement milks are to provide total nutrition, preparations should include vegetable oils, such as soybean oil, as a source of linoleic and alpha-linolenic acids, and additional vitamins and minerals.